Healing process after surgical treatment with scalpel, electrocautery and laser radiation: histomorphologic and histomorphometric analysis - Cantarelli Morosolli, Aline Rose; Veeck, Elaine Bauer; Niccoli-Filho, Walter [UNESP]; Gomes, Monica Fernandes [UNESP]; Goulart, Maria das Gracas V. [UNESP] (Springer London Ltd, 2010)
The aim of this study was to evaluate and compare the healing process after surgical treatment of chemically induced lesions in the lateral edge of tongue of hamsters performed with scalpel, electrocautery, carbon dioxide (CO(2)) laser radiation or neodymium:yttrium-aluminum-garnet (Nd:YAG) laser radiation. Eighty hamsters of both sexes were used and examined at postoperative days 7, 14, 21 and 28 by histological and histomorphometric analysis of the skeletal muscle fibers. In the histological analysis it was observed that the dynamics of the healing process was faster in the group treated by scalpel than in the other groups. The histomorphometric observation of the skeletal muscle fibers was submitted to one-way analysis of variance (ANOVA) and Tukey's multiple comparison test, with a level of significance set at P < 0.05, which showed that the amount of skeletal muscle fiber formed had significantly increased in the group treated by scalpel in comparison with that in the groups treated by electrocautery (P < 0.01), CO(2) laser irradiation (P < 0.001) and Nd:YAG laser irradiation (P < 0.01) on the 14th postoperative day. A gradual increase in skeletal muscle fibers formed during the healing process was observed in all groups. When the laser irradiated groups were compared, it was possible to conclude that tissue organization and vascularization were faster and more intense in the Nd:YAG laser irradiated group than in the CO(2) laser irradiated group.
Keywords: Lasers; Carbon dioxide; Neodymium:yttrium-aluminum-garnet (Nd:YAG); Wound healing